2007
DOI: 10.1136/adc.2006.100156
|View full text |Cite|
|
Sign up to set email alerts
|

Methamphetamine detection in maternal and neonatal hair: implications for fetal safety

Abstract: Background: Methamphetamine misuse is a serious health problem of epidemic proportions. Use of this drug, particularly during pregnancy, is difficult to ascertain. Sparse information is available on gestational exposure. Objectives: To quantify methamphetamine accumulation in hair, identify the use of methamphetamine with other drugs of abuse and characterise correlations between concentrations of methamphetamine in maternal and neonatal hair. Subjects and methods: Motherisk laboratory at the Hospital for Sick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…Garcia-Bournissen et al reported that one neonate in 11 subjects (= ca. 9%) was negative for MP in a hair sample, even though the mother was positive [5]. In a previous report that compared the sensitivity and specificity of a maternal interview, maternal hair analysis, and meconium analysis in detecting perinatal exposure to cocaine, opiates, and cannabinoids [10], meconium analysis was found to be a highly sensitivity method for detecting cocaine and opiate, and gave no false-positive results.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Garcia-Bournissen et al reported that one neonate in 11 subjects (= ca. 9%) was negative for MP in a hair sample, even though the mother was positive [5]. In a previous report that compared the sensitivity and specificity of a maternal interview, maternal hair analysis, and meconium analysis in detecting perinatal exposure to cocaine, opiates, and cannabinoids [10], meconium analysis was found to be a highly sensitivity method for detecting cocaine and opiate, and gave no false-positive results.…”
Section: Resultsmentioning
confidence: 94%
“…Fetal hair begins to form around the 20th week of gestation [5]. It has the ability to retain drugs present in the fetal circulation, in common with adult hair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Meconium is an alternative, noninvasive matrix that can be tested for drug exposure during pregnancy. 11 Drugs in fetal circulation are partially metabolized in the fetal liver and excreted into bile and urine.…”
Section: Discussionmentioning
confidence: 99%
“…Nenhuma das pacientes havia relatado o uso de drogas durante a entrevista. 17 Em estudo de Lester et al, no grupo de neonatos com mecônio positivo para cocaína e opioides, 38% das mães haviam negado o uso de drogas. 8 A análise de mecônio tem sido o método mais utilizado e suas principais vantagens são a facilidade de obtenção da amostra e a boa aceitação pelos pais.…”
Section: Metodologiaunclassified